Pre-employment HIV/AIDS test: An emerging trend of discrimination in Nigeria (2010)
HIV/AIDS has been around for over a quarter of century. The HIV/AIDS epidemic is one that knows no geographical class, caste, gender and sexual borders. The fear of discrimination has prevented many people from seeking treatment or disclosing their status openly. In the context of employment, PLWHA are often denied employment at the time of recruitment on account of their HIV status. While those already in employment are discriminated against by their co-workers and employers, and their employment are frequently terminated. This paper examines the right of persons living with HIV/AIDS and shall contend that PLWHA should not be discriminated against when applying for employment and in the course of employment